ECMELLA as a bridge to heart transplantation in refractory ventricular fibrillation: A case report - Giraud, Raphaël; Assouline, Benjamin; Burri, Haran; Shah, Dipen; Meyer, Philippe; Degrauwe, Sophie; Kirsch, Matthias; Bendjelid, Karim (Frontiers in Cardiovascular Medicine, 2023)
Background Extracorporeal membrane oxygenation (ECMO) is an effective cardiorespiratory support technique in refractory cardiac arrest (CA). In patients under veno-arterial ECMO, the use of an Impella device, a microaxial pump inserted percutaneously, is a valuable strategy through a left ventricular unloading approach. ECMELLA, a combination of ECMO with Impella, seems to be a promising method to support end-organ perfusion while unloading the left ventricle. Case Summary The present case report describes the clinical course of a patient with ischaemic and dilated cardiomyopathy who presented with refractory ventricular fibrillation (VF) leading to CA in the late postmyocardial infarction (MI) period, and who was successfully treated with ECMO and IMPELLA as a bridge to heart transplantation. Discussion In the case of CA on VF refractory to conventional resuscitation manoeuvres, early extracorporeal cardiopulmonary resuscitation (ECPR) associated with an Impella seems to be the best strategy. It provides organ perfusion, left ventricular unloading, and ability for neurological evaluation and VF catheter ablation before allowing heart transplantation. It is the treatment of choice in cases of end-stage ischaemic cardiomyopathy and recurrent malignant arrhythmias.